(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Objectives: To evaluate the type and degree of hearing loss in CSOM and also to find out any relationship between the hearing loss and disease duration. Methods: This was a cross sectional study which was carried out in the departments of Otolaryngology and Head-Neck Surgery of BSMMU and Dhaka Medical College Hospital during the period of July’2011 to December’2011. A total 80 cases of CSOM were collected. Patient below the age of 5 years and patients above the age of 50 years were excluded from this study. The diagnosis of CSOM was established on the basis of clinical examination- otoscopy and tunning fork test. Pure tone audiogram (PTA) was done for hearing assessment. Thus, 80 cases of CSOM were collected with their PTA reports of 117 ears. Results: The study included 80 patients of CSOM, of them 60 were with tubo-tympanic type and 20 were with attico-antral disease. Highest number of patients was in 2nd decade in both type of disease. 44.79% of ears of tubo-tympanic type were associated with mild (26-40 dB) hearing loss and 42.85% attico-antral variety was with moderate (41-55 dB) hearing loss. Conductive type of hearing loss was common in both types of disease. 98% of ears in tubotympanic and 81% of ears in attico-antral disease had conductive hearing loss. Mixed type (2.08%) of hearing loss was found in tubo-tympanic disease. Attico-antral disease was also associated with mixed (14.28%) and SNHL (4.76%). Conclusion: The above study revealed that hearing loss in CSOM is mostly conductive in nature rarely sensorineural in type. Bangladesh J Otorhinolaryngol; April 2017; 23(1): 59-66